Current Concepts and Future Directions in the Pharmacology and Treatment of Coccidioidomycosis. (25th January 2019) - Thompson, George R; Lewis, James S; Nix, David E; Patterson, Thomas F
Abstract: Coccidioidomycosis remains a significant clinical problem with substantial morbidity and mortality. The vast majority of infections are asymptomatic and the need for early primary therapy remains controversial. The use of triazole antifungals has improved tolerability of therapy but concerns about acute and long-term toxicities among available agents limit their use. In addition, recent findings of decreased in vitro fluconazole susceptibility to as many as 37% of Coccidioides spp. isolates raises concerns regarding optimal therapy for these infections as fluconazole is commonly used for therapy including central nervous system disease. Thus, new agents from novel antifungal classes are currently in preclinical and clinical development aimed at reducing toxicity and improving outcomes of these serious infections.